A retrospective Study of Mandibular Fracture in Children - Haidar, Ahmad A. (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: A retrospective study was done to report the incidence of mandibular fractures in children up to fifteen years of age seen in Rizgaree teaching hospital /Erbil / Kurdistan region of Iraq. Methods: The patient’s records of 62 injured child aged 0-15 years, from 1/1/ 2002 to 31/12/2008 were retrieved and relevant data was recorded and analysed. A data collection sheet was designed to record patient’s name, sex, age, site of fracture, the etiology of the injury and the method of treatment and complications. Results: The total number of patients who presented with mandibular fracture in children was 62 (78.5%). The ratio of boys to girls was 43 (69.4%) boys and 19 (30.6%) girls (2.2:1). Most of the trauma reported in age group 12-15years (46.8%). Regarding the site of fracture, condylar fracture (46.7%) was most common followed by symphesis (27.4%), dentoalveolar (14.5%), angle (8.1%) and body (3.3%). The main etiology of fracture was fall from height (54.8%). Most of the patients were treated by closed reduction (88.7%) and fixation. Conclusion: The incidence and etiology of mandibular fracture in children differs among different populations. In our study, the incidence was not very common, fall was most common cause, condylar fracture was most common. Most of the cases can be treated conventionally.